Thermal-electric model for piezoelectric ZnO nanowires. (10th June 2015) - Araneo, Rodolfo; Bini, Fabiano; Rinaldi, Antonio; Notargiacomo, Andrea; Pea, Marialilia; Celozzi, Salvatore
Abstract: The behavior of ZnO nanowires under uniaxial loading is characterized by means of a numerical model that accounts for all coupled mechanical, electrical, and thermal effects. The paper shows that thermal effects in the nanowires may greatly impact the predicted performance of piezoelectric and piezotronic nanodevices. The pyroelectric effect introduces new equivalent volumic charge in the body of the nanowire and surface charges at the boundaries, where Kapitza resistances are located, that act together with the piezoelectric charges to improve the predicted performance. It is shown that the proposed model is able to reproduce several effects experimentally observed by other research groups, and is a promising tool for the design of ultra-high efficient nanodevices.